BIOGRAFI DARMAWI PEJUANG DI KOTA PADANG PADA TAHUN 1945-1949 - Putra, Ardiansyah; Nurhuda, Ahmad; Ersi, Livia (Pendidikan Sejarah, 2013)
ABSTRACT ARDIANSYAH . 08,020,072 . Thesis . Biography Darmawi fighters in the city of Padang ( 1945-1949 ) . History Education Program . High School Teaching and Education ( STKIP PGRI ) West Sumatra . 2013. This paper is a study of thematic biography that describes the struggle Darmawi at any given time . Darmawi struggle Patriot figure who contributed in the years 1945-1949 Padang worth exploring , because it deals with the history and played a role as a fighter , regardless of big or small the role played . The purpose of this study is 1 ) to describe the life history Darmawi , 2 ) describe the involvement Darmawi maintaining independence , 3 ) describe Darmawi role in maintaining independence .The method used in this study is the historical method is done by several stages . The first phase of the heuristic either collect the relevant data through library and interviews . Literature study authors obtained posts from history books or scientific papers while interviews were conducted with a character who knows about Darmawi and writers conduct interviews with Desiani , Mansoersami and Rashid . The second phase of source criticism is to do the testing data through internal and external criticism . The third phase of the interpretation of the data . The fourth stage is to describe the data in the form of a scientific paper .. Therefore Darmawi make resolute herself struggling to maintain the independence of Indonesia .Darmawi role in maintaining the independence of Indonesia was also very large , Diman Darmawi go spy on allies who want to enter into the city of bertempu rmelawan Padang.Darmawi also allied forces were about to attack Indonesia.